2021
DOI: 10.1177/0267659121991033
|View full text |Cite
|
Sign up to set email alerts
|

Del Nido Cardioplegia in Coronary Artery Bypass Grafting Surgery: A safe, efficacious and economic alternative to St. Thomas solution; an experience from a developing nation

Abstract: Introduction: del Nido cardioplegia is a newer solution getting popular worldwide, whereas in Nepal, St. Thomas cardioplegia solution is conventionally used. There is no national recommendation on cardioplegia solutions supported by evidences from Nepalese studies. This study aimed to evaluate and compare the efficacy of these solutions in Nepalese patients undergoing coronary artery bypass grafting. Methods: Patients undergoing coronary revascularization, from May 2018 to December 2019, were randomized into S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Significant shortening of the CPB and XC times in the DNC groups compared with CBC was described in most of the analyzed studies [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] (Table 2). Four studies [18][19][20][21]…”
Section: Cardiopulmonary Bypass and Cross-clamp Timesmentioning
confidence: 86%
See 1 more Smart Citation
“…Significant shortening of the CPB and XC times in the DNC groups compared with CBC was described in most of the analyzed studies [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] (Table 2). Four studies [18][19][20][21]…”
Section: Cardiopulmonary Bypass and Cross-clamp Timesmentioning
confidence: 86%
“…Four [1,6,16,36] studies (including one RCT), all describing different types of cardiac surgeries, showed better echocardiographic parameters in the DNC group measured at different time points during hospitalization. No differences were shown in other studies comparing DNC and CBC (Table 8).…”
Section: Echocardiographic Findingsmentioning
confidence: 99%
“…St. Thomas' solution is a classic myocardial protective solution. Several studies have shown that St. Thomas' solution can reduce myocardial IRI by scavenging oxygen free radicals, inhibiting inflammation and reducing apoptosis to protect the myocardium[ 10 ]. Because St. Thomas' solution can protect the myocardium, our research group adjusted the content of K + to adapt to the internal environment of the skeletal muscle cells and then explored the role of the improved St. Thomas' solution in severe limb injury treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Recovery from ischemia and functional sustainability of the heart in patients following cardiac surgery using cardiopulmonary bypass (CPB) greatly depends upon better myocardial protection [ 1 ]. Cardioplegia is commonly used to induce and provide a depolarized diastolic cardiac arrest [ 2 ]. In the early 1990s, Del Nido cardioplegia (DNC) formulated for neonatal and pediatric cardiac surgery was introduced [ 3 ] which consists of a calcium-free and potassium-rich non-glucose-based solution with electrolyte composition identical to that of extracellular fluid, and provides longer duration of cardiac arrest [ 4 ].…”
Section: Introductionmentioning
confidence: 99%